2017
DOI: 10.1371/journal.pone.0189098
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing factors to the practice of self-medication in Brazil: Results from the National Survey on Access, Use and Promotion of Rational Use of Medicines (PNAUM)

Abstract: ObjectiveTo understand the predisposing factors that lead to the practice of self-medication and the factors associated with the use of medicines via self-medication in the adult population of Brazil.MethodsThe analyzed data are part of the National Survey on Access, Use and Promotion of Rational Use of Medicines (PNAUM), a survey whose population consisted of individual residents permanently domiciled in urban areas in Brazil. In this work, the data references the 31 573 respondents aged 20 or higher (76.2% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 22 publications
2
30
0
15
Order By: Relevance
“…Since, this is the first meta-analysis (quantitative synthesis) regarding epidemiology of self-medication in Ethiopia; we tried to compare our finding to other national surveys and reviews conducted outside of Ethiopia. The practice is far more than twice the finding reported from Brazil where the overall national prevalence was 18.3% [ 45 ].…”
Section: Discussionmentioning
confidence: 89%
“…Since, this is the first meta-analysis (quantitative synthesis) regarding epidemiology of self-medication in Ethiopia; we tried to compare our finding to other national surveys and reviews conducted outside of Ethiopia. The practice is far more than twice the finding reported from Brazil where the overall national prevalence was 18.3% [ 45 ].…”
Section: Discussionmentioning
confidence: 89%
“…However, the incidence of self-medication in other environments like the public population of Ardebil City, Iran, and European countries was 45.8% (39) and 61.6% (37), respectively. The higher incidence of selfmedication behaviors in the present study was likely related to the nature of the research community (women), as the results of numerous studies indicated the higher incidence of selfmedication among women compared to men (17,41).…”
Section: Discussionmentioning
confidence: 61%
“…Nevertheless, self-medication cannot be regarded as a completely safe action, rather it has potential risks, including misdiagnosis, increased use of medications, long-term use of medication, drug interference (13,14), delay in the search for appropriate treatment and medical advice, use of an unnecessary high dose of medication, presentation of rare, but serious and dangerous side effects, incorrect treatment selection, masking serious diseases, risk of dependence and drug abuse, resistance to antibiotics, and increased health costs due to an increase in mortality rates and increased length of hospitalization that can be problematic in some vulnerable groups, including the elderly (15). In various studies, numerous factors have been introduced to predict self-medication behaviors, including age, sex (7), marital status, depression, activity limitation, life satisfaction (10), education level, income level, place of residence and awareness level (16), past experiences of selfmedication and self-assessment of health status (17), cost saving (18), smoking and alcohol drinking, chronic illness, self-efficacy, and low drug literacy (17). Health literacy is associated with the ability of individuals to acquire, understand, and use information for health promotion (19), the situation that happens during the self-medication process according to most researchers; therefore, it seems that health literacy level is a determining factor in the occurrence of self-medication behaviors (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…As crises convulsivas decorrentes de epilepsia caracterizaram-se como os problemas de saúde mais evidentes na população estudada, mas, as outras queixas elencadas na Tabela 2 levam à reflexão sobre a dificuldade de lidar com as emoções e o desejo de suprimir sua dor e seu sofrimento através da automedicação, mesmo que ISSN: 1516-6406 Essentia (Sobral), v. 20, n. 2, 2019, p. 52-60 inicialmente prescrita por profissionais. A automedicação foi investigada em estudo que identificou 18,3% dos entrevistados que declararam tomar medicação sem recomendação médica; o número sobe para 35,5%, quando os entrevistados conhecem alguém que já tomou a medicação (PONS et al, 2017). Outra pesquisa destacou a maior frequência de automedicação entre mulheres, elas representaram 64,2% dos que responderam que se automedicam (FREITAS; MELO, 2018).…”
Section: Discussionunclassified